Effects Of “Learning To Write, Reading To Learn” Pedagogy On The Narrative Writing Skills Of Senior High School Students In China - Hu, Xiaoqing (2024)
Teaching English writing is an important part of English language teaching in Senior High School in China. Compared with English listening, speaking and reading skills, the process of English writing has more complex psychological, linguistic and cultural mechanisms, thus English teaching has always been a problem for English teachers in senior high schools in China. With the reform of National English Curriculum Standards (2017 Edition) and National College Matriculation Examination, there are problems in teaching English writing, such as quick memorization of model texts for exams, over-reliance on traditional writing methods, or students' lack of interest in English writing. The research applies "L2W, R2L" pedagogy to find out the over-reliance on traditional English writing methods’ limitations and enhance students' interest in English writing, which has become an important research issue in English writing teaching.The purpose of the research is to introduce the application of "L2W, R2L" pedagogy to the narrative genre of English writing for senior high school students of Grade Two in China.